Contribution of headmaster instructional leadership and motivation to teacher work discipline - Mila Kurniawati; Nurhijah Gustituati; Rusdinal Rusdinal (Universitas Negeri Padang, 2019)
The background of this research is still the low discipline of teacher work in SMP V Koto Kampung Dalam Pariaman. It is not yet effective that the principal's instructional leadership and teacher work motivation are still low. The purpose of this research is to know the principal of principal's principal leadership and work motivation from teacher work discipline. Data by questionnaire with likert scale that has validity and reliability. Data were analyzed by correlation and regression technique.The results showed: 1) the principal's principal leadership contributed to the teacher's work discipline of 26.1%; 2) the work motivation contributed to the teacher's work discipline of 23.6% and 3) the principal's principal leadership and work motivation jointly contributed to discipline of teacher work by 36,5%. Based on descriptive analysis revision of headmaster leadership and work motivation and teacher work discipline are both in good enough category of ideal score.